1977
DOI: 10.1136/hrt.39.12.1319
|View full text |Cite
|
Sign up to set email alerts
|

Prompt return to normal of depressed right ventricular ejection fraction in acute inferior infarction.

Abstract: A relatively simple, bedside, radionuclide technique has been developed to measure right ventricular ejection fraction. This technique uses a collimated scintillation probe (5 x 5 cm sodium iodide crystal) and 113mIndium injected into the superior vena cava to record a right ventricular time-activity curve. The radionuclide method was validated in 34 men (14 normals, 20 with coronary artery disease) with biplane right ventriculography (r= 0 82). Using this radionuclide method right ventricular ejection fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
21
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(21 citation statements)
references
References 18 publications
(1 reference statement)
0
21
0
Order By: Relevance
“…In fact, RV function is more reversible than LV function and recovers within 2-10 days after MI onset. 18,19 First, because the RV is more compliant than the LV, the Frank-Starling mechanism may work more efficiently and favorably toward ventricular remodeling in the RV compared with the LV. Second, RV function is compensated by hyperkinesis of the preserved interventricular septum, which is free of ischemia because it is independently supplied by the left anterior descending artery.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, RV function is more reversible than LV function and recovers within 2-10 days after MI onset. 18,19 First, because the RV is more compliant than the LV, the Frank-Starling mechanism may work more efficiently and favorably toward ventricular remodeling in the RV compared with the LV. Second, RV function is compensated by hyperkinesis of the preserved interventricular septum, which is free of ischemia because it is independently supplied by the left anterior descending artery.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, right ventricular systolic func tion has been systematically evaluated in the postinfarction phase [15]. Steele et al [16] reported that right ventricular ejection frac tion returned to normal from an initial de pressed value within 3 days of an acute infe rior myocardial infarction in 10 of 11 pa tients. Klein et al [17] reported the follow up radionuclide angiographic results in 37 patients who initially had evidence of de creased right ventricular ejection fraction and wall motion abnormalities.…”
Section: Right Ventricular Infarction In the Absence O F Thrombolyticmentioning
confidence: 99%
“…First, improved right ventric ular systolic function in the subacute phase may alter the filling pattern by lowering the right ventricular filling pressures and by decreasing the size of the dilated right ventricle. Right ventricular ejection fraction has been scintigraphically suggested to improve in a relatively short time after the onset of right ventricular infarction [25][26][27], In our study, although in the acute phase group 1 patients suffered from a low output state with moderate to severe hypotension, all of the patients recovered from this state in the subacute phase. Therefore, hemodynamic improvement might manifest the inherent pattern of ab normal relaxation.…”
Section: Comparison Of the Right Ventricular Filling Pattern In The Smentioning
confidence: 47%